A NOTE ON BAYESIAN ANALYSIS OF DECAPITATED GENERALIZED POISSON DISTRIBUTION UNDER VARIOUS LOSS FUNCTIONS - Dey, Sanku; Dey, Tanujit (Pakistan journal of statistics and operation research, 2011)
It is recognized that, for Bayes estimators, the performance depends on the form of the prior distribution and the assumed loss function. This paper resolves the problem of estimation of one parameter decapitated generalized Poisson distribution; using class of improper prior distributions under symmetric and asymmetric loss functions. The statistical performances of the Bayes estimates with respect to different priors and loss functions are compared using mean square error based on simulation study.